Elective course proposal on the history of the University Student Federation in Cuban medical universities - José Carlos Alvarez Hernández; Ailén Guzmán López; Yusnier Lázaro Díaz Rodríguez; Ariel Araujo Alvarez; Yohant Pazos Monte; Liliana Álvarez Ossorio (Universidad de Ciencias Médicas de Granma, 2022)
Introduction: Cuban university students are represented by the University Student Federation, in this sense, it is essential to draw up strategies that increase knowledge about the theoretical bases of this organization. Objective: to prepare a proposal for an elective course on the history of the University Student Federation in the Cuban medical sciences universities. Method: development study was carried out, qualitative, descriptive and cross-sectional approach at the Faculty of Medical Sciences of Moron, Ciego de Avila, during the months of February to March 2021. Theoretical and empirical methods were addressed. An analysis of the study plans of the Medicine, Stomatology, Nursing and Health Technologies careers was carried out for the preparation of the proposed design. Results: an elective course program on the history of the University Student Federation was developed for undergraduate students of medical sciences, in person, organized into five themes and with a duration of 60 hours distributed over seven weeks. Conclusions: the proposed elective course contributes to enhance the curricular activities that contribute to the improvement of the youngest student organization in Cuba, allowing greater visibility and representativeness of its members in each of the work fronts reflected in its governing document, the ABC of the University Student Federation.